The trend to flexible production and the precarious work in the contexto of financial capitalism - Carvalho, João Mauro Gomes Vieira (Faculdade de Ciências e Letras - Unesp - Araraquara., 2016)
This paper aims to delineate the current trends of work in the context of productive flexibility background. For that purpose, it is assumed that the work is the key element for the human socialization process and it should be comprehended in its historical specifity, and it has to be correlated to the social totality in wich it operates. In this sense, it tries to demonstrate, using theoretical studies references related to the transformations in work organization, the consequences of the current process of flexibilization of work production, by an objetctive point of view, showing the flexibilization impacts on material conditions of work and the subjecive constitution of the worker, demonstrating its impact on his political organization, his training process and the constitution of his laboral identity.element for the human socialization process and it should be comprehended in its historicalspecifity, and it has to be correlated to the social totality in wich it operates. In this sense, ittries to demonstrate, using theoretical studies references related to the transformations in workorganization, the consequences of the current process of flexibilization of work production,by an objetctive point of view, showing the flexibilization impacts on material conditions ofwork and the subjecive constitution of the worker, demonstrating its impact on his politicalorganization, his training process and the constitution of his laboral identity.